Regulation of PD-L1 Expression by NF-κB in Cancer - Antonangeli, Fabrizio; Natalini, Ambra; Garassino, Marina Chiara; Sica, Antonio; Santoni, Angela; Di Rosa, Francesca (Frontiers in Immunology, 2020)
Immune checkpoints are inhibitory receptor/ligand pairs regulating immunity that are exploited as key targets of anti-cancer therapy. Although PD-1/PD-L1 pair is one of the most studied immune checkpoints, several aspects of its biology are still to be clarified. It has been established that PD-1 is an inhibitory receptor up-regulated by activated T, B, and NK lymphocytes, and that its ligand PD-L1 mediates a negative feedback of lymphocyte activation contributing to restore steady state condition after acute immune responses. This loop might become detrimental in the presence of either a chronic infection or a growing tumor. PD-L1 expression in tumors is currently used as biomarker to orient therapeutic decision, nevertheless our knowledge about the regulation of PD-L1 expression is limited. The present review discusses how NF-κB, a master transcription factor of inflammation and immunity, is emerging as a key positive regulator of PD-L1 expression in cancer. NF-κB directly induces PD-L1 gene transcription by binding to its promoter and it can also regulate PD-L1 post-transcriptionally through indirect pathways. These processes, which in condition of cellular stress and acute inflammation drive tissue homeostasis and promote tissue healing, are largely dysregulated in tumors. Up-regulation of PD-L1 in cancer cells is controlled via NF-κB downstream of several signals, including oncogene- and stress-induced pathways, inflammatory cytokines, and chemotherapeutic drugs. Notably, a shared signaling pathway in epithelial cancers induces both PD-L1 expression and epithelial-mesenchymal transition, suggesting that PD-L1 is part of the tissue remodeling program. Furthermore, PD-L1 expression by tumor infiltrating myeloid cells contributes to the immune suppressive features of tumor environment. A better understanding of the interplay between NF-κB signaling and PD-L1 expression is highly relevant to cancer biology and therapy.